Pengaruh kepercayaan diri terhadap kemampuan komunikasi matematis siswa mts pada materi himpunan - Siti Robiah; Reni Nuraeni (Institut Pendidikan Indonesia, 2023)
In reality, students' mathematical communication skills are still low, one of the factors that influence mathematical communication skills is self-confidence. This study aims to determine the level of self-confidence, the level of mathematical communication skills, and the effect of self-confidence on students' mathematical communication skills in the set material. This research is quantitative research with correlational method. The population in this study were students of class VII MTs Al-Ma'arif Cilageni Kadungora. Sampling was done by purposive sampling technique and obtained 24 students as research samples. Data collection techniques used questionnaires to measure self-confidence and tests in the form of description questions to measure mathematical communication skills. The data analysis technique used is simple linear regression analysis and t test. The results showed that the level of self-confidence of class VII students at MTs Al-Ma'arif Cilageni Kadungora for the 2022/2023 academic year was in the moderate category. Based on the data test of mathematical communication ability, it was found that the level of mathematical communication ability of VII students of MTs Al-Ma'arif Cilageni Kadungora for the 2022/2023 academic year is in the medium category. Based on simple linear regression analysis and t test, the results of this study indicate that there is a significant effect of self-confidence on the mathematical communication skills of class VII students at MTs Al-Ma'arif Cilageni Kadungora for the 2022/2023 academic year of 87.5%, while 12.5 % influenced by other factors.Kenyataannya kemampuan komunikasi matematis siswa masih rendah, salah satu faktor yang mempengaruhi kemampuan komunikasi matematis adalah kepercayaan diri. Penelitian ini bertujuan untuk mengetahui tingkat kepercayaan diri, tingkat kemampuan komunikasi matematis, dan pengaruh kepercayaan diri terhadap kemampuan komunikasi matematis siswa pada materi Himpunan. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasional. Populasi pada penelitian ini adalah siswa kelas VII MTs Al-Ma’arif Cilageni Kadungora. Pengambilan sampel dilakukan dengan teknik purpossive sampling dan diperoleh 24 siswa sebagai sampel penelitian. Teknik pengumpulan data menggunakan angket untuk mengukur kepercayaan diri dan tes berupa soal uraian untuk mengukur kemampuan komunikasi matematis. Teknik analisis data yang digunakan adalah analisis regresi linier sederhana dan uji t. Hasil penelitian menunjukkan bahwa tingkat kepercayaan diri siswa kelas VII MTs Al-Ma’arif Cilageni Kadungora tahun ajaran 2022/2023 berada pada kategori sedang. Berdasarkan uji data kemampuan komunikasi matematis diperoleh bahwa tingkat kemampuan komunikasi matematis siswa VII MTs Al-Ma’arif Cilageni Kadungora tahun ajaran 2022/2023 berada pada kategori sedang. Berdasarkan analisis regresi linear sederhana dan uji t, hasil penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan kepercayaan diri terhadap kemampuan komunikasi matematis siswa kelas VII MTs Al-Ma’arif Cilageni Kadungora tahun ajaran 2022/2023 sebesar 87,5%, sedangkan 12,5% dipengaruhi oleh faktor lain.